2002
DOI: 10.4153/cjm-2002-016-9
|View full text |Cite
|
Sign up to set email alerts
|

Mahler’s Measure and the Dilogarithm (I)

Abstract: Abstract. An explicit formula is derived for the logarithmic Mahler measure m(P) of P(x, y) = p(x)y− q(x), where p(x) and q(x) are cyclotomic. This is used to find many examples of such polynomials for which m(P) is rationally related to the Dedekind zeta value ζ F (2) for certain quadratic and quartic fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(134 citation statements)
references
References 7 publications
3
129
0
2
Order By: Relevance
“…Such triangulations are automatically "hard"; but more seriously, they fail to describe the moduli space of flat connections on M (cf. [55], Section 10.3, and [56,57]), and should never be expected to produce the correct theory T M or its index.…”
Section: -Manifolds and 3d Indices 1005mentioning
confidence: 99%
“…Such triangulations are automatically "hard"; but more seriously, they fail to describe the moduli space of flat connections on M (cf. [55], Section 10.3, and [56,57]), and should never be expected to produce the correct theory T M or its index.…”
Section: -Manifolds and 3d Indices 1005mentioning
confidence: 99%
“…This choice, called the choice of polarization, means that one needs to pick a foliation of the phase space by Lagrangian submanifolds parametrized by a maximal set of mutually commuting "coordinates" (with the remaining variables understood as their conjugate momenta). In the problem at hand, the (complex) phase space is 2-dimensional, with the symplectic form (1.2), 34) so that the ambiguity associated with the choice of polarization is described by one functional degree of freedom, say, a choice of function f (u, v) that one regards as a "coordinate." Thus, in most of the present paper we make a natural 14 choice (1.7) treating u as the "coordinate" and v as the momentum.…”
Section: Jhep02(2012)070mentioning
confidence: 99%
“…In [9], Jones showed that irreducible representations of B n are indexed by Young diagrams, and the ones with at most two columns are the T L n representations. By abuse of notation, let T L n also denote the algebra with coefficients in Q(A), and generators and relations as in (2). The Q(A)-basis is the same Z[A ±1 ]-basis described above, so the bilinear pairing extends linearly to Q(A) such that for any tangles,…”
Section: Introductionmentioning
confidence: 99%